Energy, Ecology and Environment - Energy, Ecology and Environment (Springer Nature, 2026)
This journal offers a discipline-spanning forum for investigating shortages of natural resources, impacts on ecosystems and deterioration of the natural environment. Its coverage is focused on approaches that integrate considerations of energy, ecology and environment and that utilize its cross disciplinary integration to function as a needed counterbalance to the dominant economic approach. The journal fosters close links among these interrelated areas of investigation, to set up systems science based on knowledge from other sciences and to promote multidisciplinary solutions for tackling complex socio-economic and environmental problems. Topics covered include energy engineering and innovation for sustainability, energy storage and applications; climate dynamics, adaptation, and mitigation; environmental pollution and ecological remediation; climate change and public health; biodiversity and ecosystem services across energy transition; environmental governance and policy; data science and more. A publication of the International Society of Energy and Environmental Science.
FI 0.8
Q2
Keywords: Physical Sciences & Engineering; Energy; Ecología; Energía; Acuerdos transformativos; Transformative agreements; Cambio climático y salud pública; Biodiversidad y servicios ecosistémicos; Big data; Nanotecnología sostenible